The reliability, sensitivity and specificity of fluorescent oxidation products for measuring global oxidative stress in vivo - Bing Liang; Juan Zhang; Xue Shen; Xiaohua Zhang; Ann M. Vuong; Linghua Yang; Xinyan Shi; Xueru Ge; Huan He; Tong Liu; Shuman Yang (All Life)
Introduction To examine the reliability, sensitivity, and specificity of fluorescent oxidation products (FlOPs; markers of global oxidative damage) for measuring global oxidative stress. Methods To improve FlOP measurement reliability, we mixed plasma samples with the extractant at eight ratios and measured FlOPs with a fluorescent microplate reader (excitation/emission wavelengths 320/420 nm denoted FlOP_320; 360/420 nm [FlOP_360]; and 400/475 nm [FlOP_400]). In a human study, we examined the reliability of an improved FlOP measurement. In an animal study, we examined the sensitivity and specificity of FlOPs for measuring D-galactose induced global oxidative stress. Results At a 1:20 (plasma/extractant) mixture ratio, the overall inter-/intra-assay coefficients of variation (CV) for FlOP measurements among healthy and coronary heart disease participants were <3.6%/<2.7% and <4.4%/<2.0%, respectively. On day 30 of the animal experiment, the Pearson correlations (r) of FlOP_320 and FlOP_360 with D-galactose dose were 0.816 and 0.801, respectively, which were 3-12 times higher than those of malondialdehyde (0.183), 8-hydroxyguanosine (0.157), pentosidine (0.254), and nitrotyrosine (0.068) for measuring D-galactose-induced oxidative damage. FlOP_360 (r = 0.225, P = 0.045), but not FlOP_320 and FlOP_400, were significantly correlated with c-reactive protein, a marker of inflammation. Conclusions FlOP_320 are reliable, sensitive and specific markers for measuring global oxidative stress. Key policy highlights Fluorescent oxidation products (FlOPs) are a reliable marker of oxidative stress FlOPs at 320/420 nm are more sensitive than traditional markers FlOP at 320/420 nm did not reflect inflammation as quantified by c-reactive protein